TINJAUAN EMPIRIS BERBAGAI MODEL MANAJEMEN LABA PADA PERUSAHAAN GO PUBLIK DI INDONESIA - - Wiyadi; Rina Trisnawati; Noer Sasongko (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The article describes the earning management research had done with various models. They are aggregate discretionary accruals with modified jones model, Short-term and longterndiscretionary accruals, the real earning management with abnormal cashflow, abnormal production and abnormal discretionanry expenses as the proxies, and integratedearning management.. The sample are 130 companies listed in JII and 165 companies listed in LQ 45 during 2004-2010 period. Descriptive qualitative used to measure the mean value of these proxies, then aggregate earning management measured by ranking of them. Theresults showed that inconsistency from these analysis.The alternative method for measuring integrated earning management is needed.So, this model has riil contribution for future earning management researches. In the future, researcher will continue this model by looking for the relationship earning management with information asymmetric and agency cost to look at the earning management with opportunistic perspective and positiveperspective Keywords:  Integrated earning management, real and accruals earning management